“ONE TEACHER AT A TIME”: PROFESSIONAL PERSPECTIVES ON COACHING AND MENTORING IN EARLY CHILDHOOD EDUCATION - Graham, Lyndsey N (East Carolina University, 2020)
Coaching and mentoring are prominent approaches to supporting quality in early childhood education. Many models exist for coaching and mentoring Pre-K teachers, but few models detail what actually occurs during the coaching and mentoring process or utilize the perspective of the mentors and coaches. The Early Educator Support (EES) Program is a relatively new model of mentoring and coaching support for non-public Pre-K teachers. This study examined the lived experiences of 12 mentors and evaluators serving in the EES program through individual interviews that focused on their experience of providing support to teachers. Common themes emerged from the qualitative data analysis, including the coaching and mentoring process, strategies that support the process, and barriers, motivators, and facilitators that influence this process. The findings of this study can inform future mentor training process, assist in program development, and lend insight into the best practices that can be utilized in coaching and mentoring.
Keywords: Mentoring; Coaching; Evaluating; Early Childhood Education; Teachers